Respuesta :

Answer:

[tex]=-3[/tex]

Step-by-step explanation:

[tex]\left(-3\right)^3+\left(-4\right)^2-\left(-2\right)^3\\Follow\:the\:PEMDAS\:order\:of\:operations\\\mathrm{Calculate\:exponents}\:\left(-3\right)^3\::\quad -27\\\left(-3\right)^3\\\mathrm{Apply\:exponent\:rule}:\quad \left(-a\right)^n=-a^n,\:\mathrm{if\:}n\mathrm{\:is\:odd}\\\left(-3\right)^3=-3^3=-27\\=-27+\left(-4\right)^2-\left(-2\right)^3\\\mathrm{Calculate\:exponents}\:\left(-4\right)^2\::\quad 16\\\left(-4\right)^2[/tex]

[tex]\mathrm{Apply\:exponent\:rule}:\quad \left(-a\right)^n=a^n,\:\mathrm{if\:}n\mathrm{\:is\:even}\\\left(-4\right)^2=4^2=16\\=-27+16-\left(-2\right)^3\\\mathrm{Calculate\:exponents}\:\left(-2\right)^3\::\quad -8\\\left(-2\right)^3\\\mathrm{Apply\:exponent\:rule}:\quad \left(-a\right)^n=-a^n,\:\mathrm{if\:}n\mathrm{\:is\:odd}\\\left(-2\right)^3=-2^3=-8\\=-27+16-\left(-8\right)\\\mathrm{Add\:and\:subtract\:\left(left\:to\:right\right)}\:-27+16-\left(-8\right)\::\quad -3\\-27+16-\left(-8\right)[/tex]

[tex]-27+16=-11\\=-11-\left(-8\right)\\\mathrm{Apply\:rule\:}-\left(-a\right)\:=\:+a\\-\left(-8\right)=+8\\=-11+8\\-11+8=-3\\=-3[/tex]

The answer is -3 let me know if you need to show work